Arrest and police remand issue of top Jamaat leaders in Bangladesh: under the guise of hurting the religious sentiments of Muslims - Jalil, Md. Abdul; Rahman, Muhammad Khalilur (Canadian Center of Science and Education, 2011)
Bangladesh is a country which is located at the Southern part of the globe, Southern side of India and on the bank of the Bay-of-Bengal. It was formerly a part of Pakistan but Bangladesh is now an independent country. On 16 December 1971, Bangladesh became separated after nine months of a bloody liberation/civil war with Pakistan. The main objective of the liberation was to obtain independence so as the development of the country can be fully implemented in all aspects, as far as possible, in order to meet the needs of people who have been long ignored by the former masters. But the objectives of indepence were not that easily fulfilled because in 1972 and after numerous democratic parties were established in Bangladesh, but they still could not work together peacefully as joint partners for the development of the country. The political party leaders still have the mentality of their former masters which they have unconsciously inherited in terms of jealousy and feeling of distrust amongst themselves subsequently developing into open hostility and bloody fighting among themselves on minor differences of political ideology and policy. This paper focuses on the current scenario of social-political situation in Bangladesh.